Quantifying sustainability: A new approach and world ranking - Carlo Carraro; Lorenza Campagnolo; Fabio Eboli; Elisa Lanzi; Ramiro Parrado; Elisa Portale (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper proposes a new tool to assess sustainability and make the concept of sustainable development operational. It considers its multi-dimensional structure combining the information deriving from a selection of relevant sustainability indicators belonging to economic, social and environmental pillars. It reproduces the dynamics of these indicators over time and countries. Then, it aggregates these indicators using a new approach based on Choquet's integrals. The main novelties of this approach are indeed: (i) the modelling framework, a recursive-dynamic computable general equilibrium used to calculate the evolution of all indicators over time throughout the world, and (ii) the aggregation methodology to reconcile them in one aggregate index to measure overall sustainability. The former allows capturing the sector and regional interactions and higher-order effects driven by background assumptions on relevant variables to depict future scenarios. The latter makes it possible to compare sustainability performances, under alternative scenarios, across countries and over time. Main results show that the current sustainability at world level differs from what the traditional measure of well-being, the GDP, depicts, highlighting the trade-offs among different components of sustainability. Moreover, in the next decade a slight decrease in world sustainability may occur, in spite of an expected increase in world domestic product. Finally, dedicated policies increase overall sustainability, showing that social and environmental benefits may be greater than the correlated economic costs.
Keywords: Q54; Q56; C68; 330; Sustainable Development; Sustainable Indicators; Computable General Equilibrium; Millennium Development Goals; Climate Change; Nachhaltigkeit; Nachhaltige Entwicklung; Wirtschaftsindikator; Millennium Development Goals; Ranking-Verfahren; Welt